Hvalfangerselskapet Kosmos - Boye, Tore (Anders Jahres pengebinge, 2005)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Økonomi og økologi i ishavene - Kjeldstadli, Knut (Et splittet samfunn : 1905-1935, 2005)
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; økologi; økonomi

Sediment characterization by echosounding and sampling - Kuhn, Gerhard; Brückner, Sylvia; Didik, Claudia; Forwick, Matthias; Hass, Christian; Lensch, Norbert; Schmitt, Wolfgang; Waldthausen, Constanze V; Wittling, Thomas (The Expedition ANTARKTIS-XX of RV Polarstern in 2002/2003 Reports of Legs 1 and 2, 2005)
The reconstruction of the paleoclimatic and paleoceanographic development of the late Quaternary Southern Ocean and adjacent continental areas in high temporal and spatial resolution is a main goal of our longterm study. During ANT-XX/2 the sedimentary budget of biogenic and terrigenous components and their variability was investigated in cooperation with geochemical projects. Main objectives were the relationships between production of biogenic components and input of terrigenous components and involved nutrients.
Keywords: Sørishavet; geokjemi; marin geologi; oseanografi; paleoklimatologi

”Admiralen” til Sydishavet – et 100 års minne - Ringstad, Jan Erik (Kulturminner, 2005)
Den 21. oktober 1905 forlot flytende kokeri Admiralen og hvalbåtene Ornen og Hauken Sandefjord med kurs for Falklandsayene og Syd Shetland. Dermed innledes et nytt kapittel i den moderne hvalfangsts histone. lnitiativtaker var Christen Christensen, hovedaksjoner og disponent for Aktieselskabet "Ørnen" som eide skipene det første norske hvalfangstselskap som uttrykkelig ble startet for eventuelt innkjøp av et dampskip for innredning til koker.
Keywords: Sørishavet; historie; hvalfangstselskaper; oppdagelsesreiser; pelagisk